USAHA MERAIH LOYALITAS PELANGGAN PADA KELOMPOK USAHA JAMAAH MASJID AL ISLAMI MALANG - Joko Samboro; Zubaidi Zubaidi; Musthofa Hadi; Heru Utomo; Lina Budiarti; Mohammad Maskan (Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to identify the problems faced by small businesses within the congregation of the AL Islami Mosque, RT. 03 RW. 17 Sudimoro, Mojolangu Sub-district, Lowokwaru District, Malang City, and to provide appropriate solutions to improve knowledge and skills in the areas of Service Quality and customer loyalty. The methods used in this PKM are: observation, to observe ongoing activities, interviews, to explore problems and solutions, and simulations, to find the most appropriate solutions to the problems faced. The technology to be implemented in this PKM can be in the form of lectures, meaning participants are gathered in a specific room and given a lecture on Service Quality and Customer Loyalty. It can also take the form of practical guidance and training, discussions of field experiences, or simulations, demonstrating how businesses attract potential customers and ultimately develop loyal customers.